2000
DOI: 10.1177/1321103x0001500108
|View full text |Cite
|
Sign up to set email alerts
|

Making connections: A case study of pre-service music education students' attitudinal change to indigenous music

Abstract: Approaches to the teaching of culturally diverse music programs have become an increasing concern of international music educators in recent years. These concerns are reflected in the Australian state of New South Wales where teachers of all curriculum areas are responsible for educating all students about Aboriginal heritage and cultures. As a consequence of limited guidelines regarding the use of Aboriginal music in schools and perceived shortcomings of preservice training in providing models for the teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…An overarching theme in the research is that many teachers feel ill-equipped in relation to both content and pedagogy in relation to indigenous performing arts (Dunbar-Hall, 1997; Marsh, 2000; Murphy-Haste, 2009; Whitinui, 2010a). In an Australian study, Marsh (2000) found that many teachers cited shortcomings in their pre-service training in providing models for teaching Aboriginal music programmes as explaining their lack of confidence (Marsh, 2000). A survey in 1997 of 161 music teachers in a range of New South Wales’ schools found that only 14 per cent of teachers received pre-service training in the teaching of Aboriginal and Torres Strait Islander music (Dunbar-Hall, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An overarching theme in the research is that many teachers feel ill-equipped in relation to both content and pedagogy in relation to indigenous performing arts (Dunbar-Hall, 1997; Marsh, 2000; Murphy-Haste, 2009; Whitinui, 2010a). In an Australian study, Marsh (2000) found that many teachers cited shortcomings in their pre-service training in providing models for teaching Aboriginal music programmes as explaining their lack of confidence (Marsh, 2000). A survey in 1997 of 161 music teachers in a range of New South Wales’ schools found that only 14 per cent of teachers received pre-service training in the teaching of Aboriginal and Torres Strait Islander music (Dunbar-Hall, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In relation to indigenous musics, a way to provide this contextual understanding is to work with community members and musicians (Kennedy, 2009; Marsh, 2000; Murphy-Haste, 2009; Parsons, 1999; Power & Bradley, 2011). Such an approach calls for ‘an understanding of the context from which music arises, essential in any music teaching and learning’ (Power & Bradley, 2011, p. 36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Los entornos o colectivos receptores del servicio en proyectos de ApS coinciden en gran medida con otras propuestas socioeducativas que hacen uso de proyectos musicales comunitarios: personas mayores (ver, por ejemplo, Creech, Hallam, Varvarigou, McQueen y Gaunt, 2013;Formosa, 2013), espacios rurales (Nicholls y Sullivan, 2016), prisiones y centros de detención (Cohen, 2009) o con comunidades indígenas (Marsh, 2000). Otros colectivos receptores de experiencias musicales comunitarias con fines sociales han incluido, entre otros, comunidades de personas migrantes y refugiadas (Broeske-Danielsen, 2013;Marsh, 2012), víctimas de conflictos armados o violencia directa y/o estructural (Rodríguez-Sánchez, Odena y Cabedo-Mas, 2018).…”
Section: Discussionunclassified